(untitled) (Nexo Revista Científica, 2021)
This article presents a general classification of difference-iterative algorithms (DIA) which are increasingly being used in microprocessor control systems for industrial, scientific, and technical objects. The classification is based on taking into account the features of the DIA structures (the method of organizing convergence, the order of generating the next increments of iterated quantities, cascading and interaction of several DIA, etc.). The objective of the presented DIA classification is to give microprocessor algorithmic software developers an orientation when choosing known algorithms and prospects when developing new DIA for a specific purpose.